Iceland : Fourth Review under Stand-By Arrangement, Request for Waivers of Applicability, and Request for Establishment of Performance Criteria-Staff Report; Informational Annex; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iceland. (IMF Staff Country Reports; Country Report, 2011)
Iceland has made considerable progress under an economic program supported by the Stand-By Arrangement (SBA). Successful implementation of fiscal adjustment, effective use of capital controls, and financial sector restructuring have underpinned the recovery. Executive Directors emphasized that Iceland should continue to build up its stock of international reserves. They welcomed the new framework for corporate debt restructuring, passage of the 2011 budget, and the agreement on Icesave dispute. The IMF Board appreciated efforts in achieving program targets and granted a waiver for maintaining the economic growth of the country.